Kesalahan kala bahasa Perancis mahasiswa dengan kemampuan bahasa tingkat menengah - Putranto, Catur Priyo; Firmonasari, Aprillia (Universitas Mulawarman, 2023)
French tenses are one of the most complex and varied aspects of the language, with different verb tenses and grammatical rules that can be challenging for learners to master. The purpose of this study is to analyze the forms of errors in the use of French tenses by learners with an intermediate level of language proficiency and also the factors of these errors. The method used in this research is descriptive qualitative with a morpho-syntax approach supported by questionnaire and questionnaire distribution techniques in the data collection process. In the process of data analysis, we performed data classification technique followed by mark reading technique. After analyzing the data, it was found that most errors were found in the past tense. The forms of errors found are divided into four types, namely omission of important elements, addition of unimportant elements, misinformation, and errors in arrangement. The factors causing the errors found are linguistic and sociolinguistic factors. One of the linguistic factors found is the adjustment of each verb in French while in Indonesian it is not. Regarding the sociolinguistic factors found, one of them is the lack of time in practicing French by the respondents.